Development of antisocial behaviour - Lee, Phaik Gaik; Abdullah, Maria Chong; Elias, Habibah; Uli, Jegak (Elsevier, 2010)
Developmental psychologists have examined antisocial behaviour from many perspectives, including the academic experience, and peer relation and socio economic status. Thus, this paper focuses on the role of family relations, especially parent-child attachment, as determining factor in the development of antisocial behaviour among adolescents. Previous studies have shown that secure attachment is generally related to positive behavioural and social outcomes, while insecure attachment (ambivalent or avoidant) are often related to negative outcomes. Insecure attachment which is associated with parental negativity and rejection predicts externalizing behaviour such as aggression and disruptiveness; and internalizing behaviours; such as depression, anxiety, and social withdrawal.